How the decision making in commercialisation of university technologies have been made: A case study - Ismail, Kamariah; Cooper, Sarah; Abdul Majid, Izaidin; Wan Omar, Wan Zaidi (2010)
Commercialisation of university technology is becoming an important agenda to many governments. Innovative products will be as source of industrial innovations and creating job opportunities. Companies such as Google Incorporation, Hawlett Packard and many others are examples from university inventions. This phenomenon started in the US universities, and spread over to European and Asean universities recently. Government supports through increase in the R & D and commercialisation budgets lead to universities technologies increasing in number every year. Even though the number of university technologies keeps increasing, however, both the number and proportion of exploited technology is small. The primary aim of this paper is to explain how the decision making has been made on technology that are exploited through spin-off formations and/or through licensing to established companies, while others are not exploited. This involved exploring the factors and actors in the technology and commercialising technology in a university in Scotland, to understand the different outcomes. In total, 22 technologies from a portfolio of 82 were studied. The study employed qualitative methods incorporating a case study approach. Two samples of technology from the University technologies portfolio, one comprising technologies that were commercially exploited, and the other comprising unexploited technologies, were examined. Exploited technologies were those that were licensed to established companies, and those that were used to start new spin-off companies. This study was then supplemented with interviews with the TTO director of the University and seven other university TTO Directors. The study finds that, whether a technology is commercially exploited, and the way in which it is exploited is influenced by three main factors: the motivation and commitment of the entrepreneurs and the inventors, the characteristics and nature of the technologies; and the TTOs’roles.The study finally suggests proposals for how TTOs can enhance their decision-making process, regarding which discoveries to technology in order to improve the overall effectiveness of commercialisation process in universities.